Investigation of the thoracic aorta in cholesterol embolism by transoesophageal echocardiography. Issue 2 (1st February 1998) - Ferrari, E; Taillan, B; Drai, E; Morand, P; Baudouy, M
Abstract : Objectives: To examine the thoracic aorta of patients with severe cholesterol embolism (CE) by transoesophageal echocardiography (TOE). Methods: The thoracic aorta of 20 consecutive patients with CE was compared with that in a control population matched for age and risk factors by TOE. Patients were prescribed steroids after CE was diagnosed. Follow up is reported and compared with results in the literature. Results: Aortic plaques and debris were more common in patients with CE than in the control population (p < 0.001 and p < 0.0001, respectively). The mean (SD) number of aortic plaques in the CE patients was 2.6 (0.7). This aortic atheroma was found predominantly in the descending aorta. One patient died during a mean (SD) follow up of 24 (10) months. Conclusions: Aortic atheroma, as detected by TOE, should be considered as the main source of CE. In addition, the prognosis in our series, in which steroids were systematically prescribed, is much better than in others reported in the literature.